RISK FACTORS OF WORK STRESS ON FIREFIGHTERS - Sianturi, Kristiani; Handayani, Rini; Handayani, Putri; Keumala Muda, Cut Alia (Journal of Vocational Health Studies, 2021)
Background: Firefighters.are often under pressure and get complaints from the public when extinguishing fires. They are often having heavy workloads and time targets to extinguish fires. It makes them have work stress. The initial survey showed of 80% firefighters having moderate-heavy work stress. Purpose: The aim was to know the risk factors of work stress in Firefighters in West Jakarta in 2019. Method: The research design used a cross-sectional design study. The population and samples are 105 Firefighters in West Jakarta (total sampling). The analysis was done in bivariate which was used the chi-square test. Result: The proportion of moderate-heavy work stress in Firefighters is 60.9%. Bivariate analysis show that there are relation of age (p-value < 0.001) interpersonal relationship (p-value = 0.014), and mental workload (p-value = 0.004) with work stress on Firefighters. It also show that there are no relation between level of education (p-value = 0.163), marital status (p-value = 0.071) and years of service (p-value = 0.351) with work stress on firefighter. Conclusion: The risk factors of work stress in firefighters are age, interpersonal relationships, and mental workloads.